Epidemiologia delle resistenze di Helicobacter pylori alle sostanze antibatteriche piú utilizzate nella terapia di eradicazione (Ospedale di Merano 1998 – 2002) - Mario V. Zanetti (Microbiologia Medica, 2003)
Bacterial resistance to antibiotics represents one of the most important factors of treatment failure for infectious diseases. In Helicobacter pylori (HP) infection, this aspect is of dramatic importance when considering eradication therapy which according to the most recent consensus conference implies an association of a proton pump inhibitor (PPI) and two antibiotics (mainly nitromidazoles, macrolides and beta-lactames). Beside the strong recommendation after treatment failure, in-vitro test of resistance of the mostly used antibiotics, has gained also an increasing importance over time due to the progressive increase of resistance observed with most used substances as, for example, macrolides. Metronidazole (MTR) and Clarithromycin (CLA) are almost routinely tested in our laboratory in cultures from HPpositive gastric biopsies using the disk diffusion technique (fig. 1), in-vitro resistance to Amoxicillin (AMX) is only tested if specifically requested from the clinician. A retrospective analysis of culture results from gastric biopsies taken during gastroscopy performed in the endoscopy unit of our hospital over the last quinquennial, allowed us to monitor the prevalence of HP resistance to MTR e CLA and to assess their possible relationship with age and gender. Furthermore we studied the impact of resistance on typer of eradication therapy as well as the onset of secondary resistance and the stability of CLA resistance. We have therefore considered an overall number of 1039 HP-positive cultures. Among them, 54,3% were resistant to both antibiotics being 34,7% resistant to MTR, and 18,6% resistant to CLA, and 12,1% resistant to both substances (fig.2). According to gender, data on antibiotic resistance of HP, show no difference for CLA (17,2% for and 20,1% for ), whereas MTR resistance is significantly more frequently observed in women ( 29,3% for and 40,1%). This result may probably be related to the use of MTR by ginecologist for pelvic infection. Based on the antibiotic association, it may be speculated a synergic activity of the combination of MTR and CLA. In a group of patients (n= 19) after eradication failure, a secondary antibiotic resistance was observed in 36,9%; namely 21,1% for MTR and 15,8% for CLA. In-vitro stability of resistance of the latter substance was 59,1%.